CFD SIMULATION OF BUBBLE COLUMN REACTOR BY INVESTIGATING THE EFFECT OF TRAYS ON OVERALL GAS HOLDUP - Khan, Arif; Sharif, Samrana; K. Wardag, A. N.; Chughtai, I. R.; Al-Dahhan, M. H. (The Nucleus, 2020)
In the current research work, CFD model has been developed to estimate overall gas holdup for co-current air-water system in a Trayed Bubble Column Reactor (TBCR), operating in bubbly flow regime. The TBCR considered in this study has 19 cm inner diameter and 274 cm length. Unsteady 2d-axi symmetric, Eulerian-Eulerian multiphase model with segregated solver has been considered while turbulence effects are introduced by using generalized k-ε model with the option of each-phase turbulence model. The effect of trays has been studied on overall gas holdup while liquid superficial velocity, tray’s open area and bubble diameter have been kept constant. Simulations have been performed for various values of superficial gas velocities in the range of 1-8 cm/s and constant superficial liquid velocity of 0.5 cm/sec. The overall gas holdups found by simulations, have been compared with experiments [1] and with internationally published correlations for bubble column reactors by Kato et al. [5], Chen et al. [2] and Vinaya et al. [8], which shows a fair concurrence of the CFD results. It is found that overall gas holdup significantly increases by introducing trays to the column.